Composite porous body, separation membrane and method for producing composite porous body

By covering the crosslinked polymer coating with silicon-oxygen bonds on the polytetrafluorovinyl base material to form a composite pore material, the problem of insufficient filtration speed during liquid separation in the prior art is solved, and efficient liquid permeability is achieved.

JP2025042925APending Publication Date: 2025-03-28SUMITOMO ELECTRIC INDUSTRIES LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023150132
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the prior art is used for separation of liquids rather than gases, the filtration speed is insufficient or impermeable, making it difficult to meet the demand for liquid separation.

Method used

A composite pore material formed by a base material made of polytetrafluoroethylene (PTFE) is used as the base layer and a layer of crosslinked polymer with silicon oxygen bonds is covered as the coating. The coating has a thickness of between 10 nm and 2000 nm and a pore size of between 50 nm and 500 nm, enhancing the thermal and chemical stability of the material.

Benefits of technology

It achieves high filtration speed and good liquid permeability during liquid separation, and is suitable for various liquid separation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042925000001_ABST
    Figure 2025042925000001_ABST
Patent Text Reader

Abstract

To provide a composite porous body which enables provision of a separation membrane having a good fluid permeation rate when being used as a material of the separation membrane, a separation membrane having a good fluid permeation rate, and a method for producing a composite porous body.SOLUTION: A composite porous body includes a base material having a first surface, and a coating layer coating at least a part of the first surface, wherein the base material is a porous body composed of polytetrafluoroethylene, the coating layer is composed of a crosslinked polymer compound having a siloxane bond, average thickness of the coating layer is 10 nm or more and 2,000 nm or less, and an average pore diameter on the first surface of the base material is 50 nm or more and 500 nm or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composite porous body, a separation membrane, and a method for producing a composite porous body. [Background technology]

[0002] Porous bodies made of polytetrafluoroethylene are used in various separation membranes such as filtration filters.

[0003] Patent Document 1 discloses a gas separation membrane in which an organopolysiloxane crosslinked membrane is provided on a porous support membrane. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-208079 A Summary of the Invention

[0005] The composite porous body of the present disclosure is A substrate having a first surface and a coating layer covering at least a portion of the first surface, The substrate is a porous body made of polytetrafluoroethylene, The coating layer is made of a crosslinked polymer compound having a siloxane bond, The average thickness of the coating layer is 10 nm or more and 2000 nm or less, The substrate is a composite porous body, the average pore size of which on the first surface is 50 nm or more and 500 nm or less. [Problem to be solved by the invention]

[0006] Since Patent Document 1 is a gas separation membrane, when used to separate a substance from a fluid other than a gas (for example, a liquid), the fluid permeation rate is insufficient or the fluid does not permeate. For this reason, there is a demand for a composite porous body that, when used as a material for a separation membrane, can provide a separation membrane having a good fluid permeation rate even when the fluid is other than a gas, a separation membrane having a good fluid permeation rate, and a method for producing the composite porous body.

[0007] Therefore, an object of the present disclosure is to provide a composite porous body that, when used as a material for a separation membrane, can provide a separation membrane having a good fluid permeation rate, a separation membrane having a good fluid permeation rate, and a method for manufacturing a composite porous body. [Means for solving the problem]

[0008] The composite porous body of the present disclosure is A substrate having a first surface and a coating layer covering at least a portion of the first surface, The substrate is a porous body made of polytetrafluoroethylene, The coating layer is made of a crosslinked polymer compound having a siloxane bond, The average thickness of the coating layer is 10 nm or more and 2000 nm or less, The composite porous body has an average pore size of 50 nm or more and 500 nm or less on the first surface of the substrate. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a composite porous body that, when used as a material for a separation membrane, can provide a separation membrane having a good fluid permeation rate, a separation membrane having a good fluid permeation rate, and a method for manufacturing a composite porous body. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic view of the composite porous body according to the first embodiment. [Diagram 2]FIG. 2 is a cross-sectional view of the composite porous body according to the first embodiment. [Diagram 3] FIG. 3 is a schematic diagram of a test device used in the fluid flow test. [Figure 4] FIG. 4 is a schematic view of the composite porous body according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The composite porous body of the present disclosure is A substrate having a first surface and a coating layer covering at least a portion of the first surface, The substrate is a porous body made of polytetrafluoroethylene, The coating layer is made of a crosslinked polymer compound having a siloxane bond, The average thickness of the coating layer is 10 nm or more and 2000 nm or less, The substrate is a composite porous body, the average pore size of which on the first surface is 50 nm or more and 500 nm or less.

[0012] According to the present disclosure, it is possible to provide a composite porous body that, when used as a material for a separation membrane, can provide a separation membrane having a good fluid permeation rate.

[0013] (2) In the above (1), the crosslinked polymer compound may be polydimethylsiloxane, which improves the heat resistance and chemical resistance of the composite porous body.

[0014] (3) In the above (1) or (2), the coating layer may have an average pore size of 1 nm or more and 50 nm or less, thereby making it possible to reduce the size of substances that the composite porous body can remove from a fluid to be filtered.

[0015] (4) In any one of the above (1) to (3), the average thickness of the substrate may be 1 μm or more and 100 μm or less, thereby improving the fluid permeation rate.

[0016] (5) In any one of the above (1) to (4), the coating layer may have an average thickness of 10 nm or more and 180 nm or less, thereby improving the fluid permeation rate.

[0017] (6) In any one of the above (1) to (5), the substrate may be in the form of a sheet. The composite porous body having the sheet-like substrate has an overall shape of a sheet. The sheet-like composite porous body is easily processed into various shapes and is applicable to filtration devices of various forms.

[0018] (7) In any one of the above (1) to (5), the substrate has a tube shape, The first surface may be an outer circumferential surface of the tube.

[0019] The overall shape of the composite porous body comprising a tubular substrate is tubular. The tubular substrate also includes a hollow fiber membrane. In the tubular composite porous body, a fluid containing impurities is circulated to the outside of the tubular composite porous body. A fluid that has permeated the composite porous body is circulated inside the tubular composite porous body. With the configuration described in (7) above, the composite porous body itself can form a fluid flow path. A purification device module can be formed by bundling a plurality of such composite porous bodies.

[0020] (8) In any one of the above (1) to (7), the base material comprises a first layer including the first surface and a second layer adjacent to the first layer; The second layer may have an average pore size greater than the average pore size of the first layer.

[0021] The thicker the substrate, the stronger the substrate and the stronger the composite porous body. On the other hand, the liquid permeability of the substrate decreases, and the liquid permeability of the composite porous body also decreases. The liquid permeability of substrate X having a second layer with a large average pore size is superior to that of substrate Y having the same thickness as substrate X and consisting of only the first layer. Therefore, by forming the substrate from the first layer and the second layer, the fluid permeation rate of the composite porous body is unlikely to decrease even if the substrate is made thick.

[0022] (9) A separation membrane according to the present disclosure is a separation membrane comprising the composite porous body according to any one of (1) to (8) above, The separation membrane is a pervaporation membrane or a vapor filtration membrane.

[0023] According to the present disclosure, it is possible to provide a pervaporation or vapor filtration membrane that has good fluid transmission rates.

[0024] (10) A separation membrane according to the present disclosure is a separation membrane comprising the composite porous body according to any one of (1) to (8) above, The separation membrane is an ultrafiltration membrane, a microfiltration membrane, a nanofiltration membrane or a particle separation membrane.

[0025] According to the present disclosure, it is possible to provide an ultrafiltration membrane, a microfiltration membrane, a nanofiltration membrane or a particle separation membrane having a good fluid permeation rate.

[0026] (11) The method for producing a composite porous body according to the present disclosure includes: A method for producing a composite porous body according to any one of (1) to (8), comprising the steps of: A step A of preparing a substrate having a first surface, the substrate being made of a porous material made of polytetrafluoroethylene; A step B of preparing a coating liquid containing a compound having a siloxane bond; A step C of applying the coating liquid to at least a portion of the first surface; A step D of crosslinking a portion of the coating liquid applied to the substrate; and a step E of washing away the coating liquid that has been applied to the substrate and that has not been crosslinked and remains in the step D to form a coating layer that covers at least a portion of the first surface of the substrate, thereby obtaining a composite porous body. This is a method for producing a composite porous body, wherein the time from the end of step D to the start of step E is 48 hours or less.

[0027] According to the present disclosure, it is possible to provide a method for producing a composite porous body having a good fluid permeation rate.

[0028] (12) In (11) above, In the step D, the coating liquid may be irradiated with plasma to crosslink a part of the coating liquid.

[0029] According to this method, radicals are introduced to the outermost surface of the coating liquid applied to the substrate, and the radicals act as starting points for crosslinking of the coating liquid only in the vicinity of the outermost surface of the coating liquid, making it easy to obtain a thin coating layer.

[0030] [Details of the embodiment of the present disclosure] Specific examples of the composite porous body, separation membrane, and manufacturing method of the composite porous body of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. In addition, the dimensional relationships of the length, width, thickness, depth, etc. are appropriately changed for clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.

[0031] In this specification, the expression "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.

[0032] In the present specification, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, it is understood to include any conventionally known atomic ratio, and is not necessarily limited to only those within the stoichiometric range.

[0033] In the present disclosure, when one or more numerical values ​​are described as the lower limit and the upper limit of a numerical range, a combination of any one numerical value described as the lower limit and any one numerical value described as the upper limit is also disclosed. For example, when a1 or more, b1 or more, and c1 or more are described as the lower limit, and a2 or less, b2 or less, and c2 or less are described as the upper limit, a1 or more and a2 or less, a1 or more and b2 or less, a1 or more and c2 or less, b1 or more and a2 or less, b1 or more and b2 or less, b1 or more and c2 or less, c1 or more and a2 or less, c1 or more and b2 or less, and c1 or more and c2 or less are disclosed.

[0034] [Embodiment 1: Composite Porous Body] <Overall composition> The composite porous body 1 according to the first embodiment can be in the form of a sheet as shown in FIG. 1. The composite porous body 1 includes a substrate 2 and a coating layer 12. The substrate 2 has a sheet shape. As shown in FIG. 1 and FIG. 2, the substrate 2 includes a first surface 21 and a second surface 22 opposite to the first surface 21. The coating layer 12 is provided so as to cover at least a part of the first surface 21 of the substrate 2. The average pore size of the coating layer 12 is smaller than the average pore size of the substrate 2. In addition, a nonwoven fabric made of polyethylene, polypropylene, polyester, polytetrafluoroethylene, or the like may be fused to the second surface 22 of the substrate 2. When the nonwoven fabric is fused, deformation in the surface direction of the substrate 2 is suppressed, and even if the pressure during separation is high, damage such as cracks is unlikely to occur in the coating layer. Hereinafter, each component of the composite porous body 1 will be described in detail.

[0035] <Base material> In the first embodiment, the substrate 2 is a porous body made of polytetrafluoroethylene (PTFE). As shown in Fig. 2, the substrate 2 has a plurality of pores 2h. Since Fig. 2 is a cross-sectional view, each pore 2h in the substrate 2 appears to be independent, but each pore 2h is connected to other pores 2h to form an infinite number of flow paths extending from the first surface 21 to the second surface 22. An infinite number of flow paths extending from the first surface 21 to the second surface 22 are formed in the substrate 2.

[0036] The substrate 2 is made of polytetrafluoroethylene (PTFE). PTFE has excellent heat resistance and chemical resistance. Therefore, the heat resistance and chemical resistance of the composite porous body are improved. The substrate 2 may contain components other than polytetrafluoroethylene as long as the effects of the present disclosure are not impaired. Examples of such components include perfluoroalkoxyalkane (PFA) and tetrafluoroethylene-hexafluoropropylene copolymer (FEP).

[0037] The average pore size in the first surface 21 of the substrate 2 is 50 nm or more and 500 nm or less. When the average pore size in the first surface 21 of the substrate 2 is 50 nm or more, the composite porous body 1 including the substrate 2 has excellent liquid permeability and improves the fluid permeation rate. When the average pore size in the first surface 21 of the substrate 2 is 50 nm or more, when the coating layer 12 is formed on the first surface 21 of the substrate 2, the raw material of the coating layer 12 appropriately penetrates into the substrate 2 through the pores formed in the first surface 21, and the adhesion between the substrate 2 and the coating layer 12 is improved.

[0038] If the average pore size on the first surface 21 of the substrate 2 is 500 nm or less, then when forming the coating layer 12 on the first surface 21 of the substrate 2, the raw material for the coating layer is prevented from excessively penetrating into the interior of the substrate 2 through the pores formed on the first surface 21, making it easy to form a thin coating layer 12 with excellent liquid permeability on the first surface 21. If the average pore size on the first surface 21 of the substrate 2 is 500 nm or less, the composite porous body 1 including the substrate 2 has excellent strength.

[0039] The lower limit of the average pore size on the first surface 21 of the substrate 2 may be 70 nm or more, 100 nm or more, or 130 nm or more. The larger the lower limit of the average pore size, the higher the permeation rate and the higher the processing amount per unit time, which is desirable. The upper limit of the average pore size on the first surface 21 of the substrate 2 may be 400 nm or less, 300 nm or less, or 270 nm or less. The smaller the upper limit of the average pore size, the higher the strength of the substrate 2 and the less likely the coating layer is to be destroyed even if the pressure during separation increases. The average pore size on the first surface 21 of the substrate 2 may be 70 nm or more and 400 nm or less, 100 nm or more and 300 nm or less, or 130 nm or more and 270 nm or less, in order to achieve both the strength and the permeation rate of the substrate. The average pore size on the first surface 21 of the substrate 2 is larger than the average pore size of the coating layer 12.

[0040] A plurality of pores 2h are formed on the first surface 21. When the coating layer 12 is formed on the first surface 21, it is difficult to measure the average pore diameter of the pores 2h on the first surface 21. In this disclosure, the average pore diameter on the first surface 21 of the substrate is obtained from an SEM image of a cross section along the thickness direction of the substrate 2. In this disclosure, the thickness direction of the substrate 2 means the direction from the first surface 21 to the second surface 22. The magnification of the SEM image is 5000 times. The size of the SEM image is 8 μm × 11 μm. The SEM image is binarized, and each pore 2h in the SEM image is extracted. In the SEM image, a first region between the first surface 21 of the substrate and a virtual line with a distance of 1 μm from the first surface 21 to the substrate side is specified. In the first region, the circle equivalent diameter of each pore 2h is obtained, and the arithmetic average of the circle equivalent diameters of all the pores 2h is obtained. The circle equivalent diameter is the diameter of a perfect circle having the same size as the area of ​​the pore 2h. The arithmetic mean of the circle equivalent diameters is regarded as the average pore size on the first surface 21 of the substrate 2 .

[0041] The thickness of the substrate 2 is the length between the first surface 21 and the second surface 22. The average thickness of the substrate 2 may be 1 μm or more and 100 μm or less. A composite porous body 1 having a substrate 2 with an average thickness of 1 μm or more has excellent strength. A composite porous body 1 having a substrate 2 with an average thickness of 100 μm or less has excellent flexibility. In addition, a decrease in the liquid permeation rate of the composite porous body 1 is suppressed. The lower limit of the average thickness of the substrate 2 may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. The upper limit of the average thickness of the substrate 2 may be 90 μm or less, 80 μm or less, or 50 μm or less. The average thickness of the substrate 2 may be, for example, 5 μm or more and 100 μm or less, 10 μm or more and 90 μm or less, 15 μm or more and 80 μm or less, or 20 μm or more and 50 μm or less.

[0042] The average thickness of the substrate 2 is obtained from an SEM image of a cross section along the thickness direction of the substrate 2. For the measurement, a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) is used. The magnification of the SEM image is 10,000 times. The size of the SEM image is 8 μm×11 μm. The boundary between the substrate 2 and the coating layer 12 can be confirmed in the SEM image. The distance from the boundary to the second surface 22 of the substrate 2 is the thickness of the substrate 2. The average thickness of the substrate 2 is the average of the thicknesses at five or more different points on the substrate 2.

[0043] The substrate 2 may have a plurality of layers as shown in FIG. 2. The substrate 2 may have a first layer 2A and a second layer 2B. In FIG. 2, the boundary between the first layer 2A and the second layer 2B is shown by a two-dot chain line. The first layer 2A includes a first surface 21. The second layer 2B is adjacent to the first layer 2A and includes a second surface 22. The average pore size of the second layer 2B is larger than that of the first layer 2A. The liquid permeability of the substrate 2 including the second layer 2B having a larger average pore size is superior to that of the substrate 2 having the same thickness as the substrate 2 and consisting only of the first layer 2A. Therefore, since the substrate 2 is composed of the first layer 2A and the second layer 2B, the permeation rate of the fluid through the composite porous body 1 is unlikely to decrease even if the substrate 2 is made thick. The average pore size of the second layer 2B may be, for example, 2 times to 2000 times, or 10 times to 1000 times, the average pore size of the first layer 2A. The average pore size of the first layer 2A is larger than the average pore size of the coating layer 12. When the substrate 2 is composed of three or more layers, the average pore size may be larger the further from the first surface 21. Unlike this example, the substrate 2 may be composed of only the first layer 2A. In this case, the first layer 2A includes the first surface 21 and the second surface 22.

[0044] The average pore size of the first layer 2A and the average pore size of the second layer 2B are obtained from an SEM image of a cross section along the thickness direction of the substrate 2. The first layer 2A and the second layer 2B are heat-sealed when the substrate 2 is produced. Therefore, the boundary between the first layer 2A and the second layer 2B can be confirmed in the SEM image. In the SEM image, the arithmetic mean of the circle-equivalent diameters of the pores 2h present in the region including the first surface 21 across the boundary is the average pore size of the first layer 2A. Similarly, in the SEM image, the arithmetic mean of the circle-equivalent diameters of the pores 2h present in the region including the second surface 22 across the boundary is the average pore size of the second layer 2B.

[0045] The average pore size of the first layer 2A and the average pore size of the second layer 2B are measured by the following procedure. In the SEM image, a rectangular measurement area of ​​1 μm×11 μm or more is provided in each of the first layer 2A and the second layer 2B. The arithmetic mean of the circle-equivalent diameter of each pore 2h present in the measurement area in the first layer 2A is calculated. In the present disclosure, the arithmetic mean corresponds to the average pore size of the first layer 2A. The arithmetic mean of the circle-equivalent diameter of each pore 2h present in the measurement area in the second layer 2B is calculated. In the present disclosure, the arithmetic mean corresponds to the average pore size of the second layer 2B. As far as the applicant measures, it has been confirmed that there is no variation in the measurement results even if the location of the measurement area is changed.

[0046] <Coating layer> In the first embodiment, the coating layer 12 is made of a crosslinked polymer compound having a siloxane bond. The coating layer 12 only needs to cover at least a part of the first surface of the base material 2, and may cover the entire first surface of the base material 2.

[0047] In the present disclosure, the crosslinked polymer compound having a siloxane bond has a main chain of a siloxane bond (-Si-O-Si-) and has an organic group such as a methyl group, a vinyl group, or a phenyl group on a side chain or terminal. The crosslinked polymer compound having a siloxane bond has excellent heat resistance and chemical resistance. Therefore, the heat resistance and chemical resistance of the composite porous body are improved.

[0048] It can be confirmed by the following procedure that the coating layer 12 is made of a crosslinked polymer compound having a siloxane bond. An FT-IR spectrum of the coating layer 12 is obtained by Fourier transform infrared spectroscopy (FT-IR). In the FT-IR spectrum, -1 When a peak derived from a Si-O-Si bond is present in the spectrum, it is confirmed that the coating layer 12 contains a siloxane bond. A polymer compound containing a siloxane bond is usually a liquid. Therefore, when the polymer compound exists as the coating layer 12, which is a solid film, it is determined that the polymer compound is crosslinked.

[0049] Examples of crosslinked polymer compounds having siloxane bonds include polydimethylsiloxane (PDMS), phenylmethylsiloxane, vinyl-terminated polydimethylsiloxane, trimethoxysilyl-terminated polydimethylsiloxane, and hexamethyldisiloxane (HMDSO).

[0050] The crosslinked polymer compound may be polydimethylsiloxane. Whether the crosslinked polymer compound is polydimethylsiloxane is confirmed by performing composition analysis of the coating layer 12 by X-ray photoelectron spectroscopy (XPS). Specifically, when the element ratio is C:O:Si=45-55:20-30:20-30 as a result of the composition analysis by XPS, it is confirmed that the crosslinked polymer compound is polydimethylsiloxane. The composition of crosslinked polymer compounds other than polydimethylsiloxane can also be confirmed by composition analysis by XPS.

[0051] The coating layer 12 may contain components other than the crosslinked polymer compound having a siloxane bond, as long as the effects of the present disclosure are not impaired. Examples of such components include polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), and tetrafluoroethylene-hexafluoropropylene copolymer (FEP). The content of other components in the coating layer 12 may be, for example, 50 mass% or less.

[0052] <Average thickness of coating layer> The average thickness of the coating layer 12 is 10 nm or more and 2000 nm or less. When the average thickness of the coating layer 12 is 10 nm or more, the coating layer 12 does not break during pressure filtration, and impurities are easily separated. When the average thickness of the coating layer 12 is 2000 nm or less, the fluid permeation rate of the composite porous body 1 including the coating layer 12 is improved. When the average thickness of the coating layer 12 is 2000 nm or less, the composite porous body 1 including the coating layer 12 is excellent in flexibility. The lower limit of the average thickness of the coating layer 12 may be 20 nm or more, 30 nm or more, or 50 nm or more. The larger the lower limit of the average thickness of the coating layer 12, the higher the pressure resistance, which is desirable. The upper limit of the average thickness of the coating layer 12 may be 1000 nm or less, 500 nm or less, 180 nm or less, or 140 nm or less. The smaller the upper limit of the average thickness of the coating layer 12, the higher the permeation flow rate and the better the flexibility, which is desirable. The average thickness of the coating layer 12 may be in the range of, for example, 20 nm to 1000 nm, 30 nm to 500 nm, 10 nm to 180 nm, or 50 nm to 140 nm. When the average thickness of the coating layer 12 is in the above range, it is desirable for the coating layer 12 to have pressure resistance, permeation flow rate, and flexibility.

[0053] The average thickness of the coating layer 12 is obtained from an SEM image acquired at the same upper limit as the SEM image used to measure the average thickness of the substrate. SEM-EDX is used for the measurement. The magnification of the SEM image is 10,000 times. The size of the SEM image is 8 μm × 11 μm. On the SEM image, the distance from the boundary between the first surface 21 of the substrate 2 and the coating layer 12 to the surface 30 of the coating layer 12 is the thickness of the coating layer 12. Even if the same component as the coating layer 12 is present inside the substrate 2 from the first surface 21 of the substrate 2, the thickness of the coating layer 12 is the distance from the boundary between the first surface 21 of the substrate 2 and the coating layer 12 to the surface 30 of the coating layer 12, and does not include the thickness of the same component as the coating layer 12 present inside the substrate 2. The average thickness of the coating layer 12 is the average thickness of five different points in the coating layer 12. If there are recesses due to voids 2h on the first surface 21 of the substrate 2, the recesses are excluded from the measurement points.

[0054] <Average pore size of coating layer> The average pore size of the coating layer 12 may be 1 nm or more and 50 nm or less. When the average pore size of the coating layer 12 is 1 nm or more, the filtration time by the composite porous body 1 is not too long. When the average pore size of the coating layer 12 is 50 nm or less, the permeation rate and the separation performance can be compatible, and the impurities can be efficiently separated by the coating layer 12. The lower limit of the average pore size of the coating layer 12 may be 2 nm or more, or 5 nm or more. The larger the lower limit of the average pore size, the more desirable it is because the permeation rate of the fluid is improved. The upper limit of the average pore size of the coating layer 12 may be 45 nm or less, 40 nm or less, or 30 nm or less. The smaller the upper limit of the average pore size, the more desirable it is because the permeation rate and the separation performance can be compatible. The range of the average pore size of the coating layer 12 may be 2 nm or more and 45 nm or less, or 5 nm or more and 40 nm or less. When the average pore size is in the above range, the permeation rate and the separation performance can be compatible, and it is therefore desirable. The average pore size of the coating layer 12 is smaller than the average pore size of the substrate 2 .

[0055] The average pore size of the coating layer 12 is very small, and therefore difficult to determine from an SEM image of the cross section of the coating layer 12. In the present disclosure, the average pore size of the coating layer 12 is determined by a liquid passage test. FIG. 3 is a schematic diagram of a test apparatus 7 used in the liquid passage test. The test apparatus 7 includes a flask 70 that can be evacuated and a cylindrical chamber 71 that is open at both ends. The composite porous body 1 is sandwiched between a lower opening 71D of the chamber 71 and an upper opening 70U of the flask 70. The coating layer 12 of the composite porous body 1 faces the chamber 71.

[0056] The procedure for determining the average pore size of the coating layer 12 is as follows. First, a test liquid containing a plurality of particles having a known average particle size is prepared. Here, the average particle size means the mode of the particle number distribution. The particle concentration (g / cm) in the test liquid is calculated. 3) is known. A number of test solutions with different average particle sizes are prepared. For example, when the average particle size is between 1 nm and 20 nm, test solutions with average particle sizes of 1 nm, 5 nm, 10 nm, and 15 nm are prepared. When the average particle size is between 20 nm and 60 nm, test solutions are prepared at 10 nm intervals. When the average particle size is between 60 nm and 100 nm, test solutions are prepared at 20 nm intervals. For the multiple particles contained in each test solution, when the average particle size is 1 nm, "2,9,16,23-tetra-tert-butyl-29H,31H-phthalocyanine" (hereinafter referred to as phthalocyanine) manufactured by Aldrich is used, and when the average particle size is between 5 and 100 nm, "gold nanoparticles" manufactured by Aldrich are used.

[0057] The test liquid is placed in a chamber 71. The flask 70 is evacuated, and the filtrate that has permeated the composite porous body 1 is stored in the flask 70. The degree of vacuum is 80 Pa or less. The particle concentration (g / cm 3 ) is measured. The concentration of particles contained in the filtrate is calculated from the measured volume of the filtrate and the mass of particles remaining after the filtrate is evaporated. The above procedure is used to perform the liquid flow test, starting with the test liquid with the smallest average particle size. The smallest average particle size among the average particle sizes of the test liquids in which the particle concentration in the filtrate is 10% or less of the particle concentration in the test liquid is regarded as the average pore size of the coating layer 12. For example, when the particle concentration in the filtrate is 90% of the particle concentration in the test liquid in a test liquid with an average particle size of 10 nm, when the particle concentration in the filtrate is 5% of the particle concentration in the test liquid in a test liquid with an average particle size of 15 nm, and when the particle concentration in the filtrate is 5% of the particle concentration in the test liquid in a test liquid with an average particle size of 25 nm, the average pore size of the coating layer 12 is 15 nm.

[0058] The ratio of the average pore size of the coating layer 12 to the average pore size on the first surface 21 of the substrate 2 is, for example, 0.01 or more and 1 or less. When the ratio is 0.01 or more, the difference between the average pore size on the first surface 21 of the substrate 2 and the average pore size of the coating layer 12 is not too large, and the coating layer 12 is easily configured appropriately on the first surface 21. When the ratio is 1 or less, the average pore size of the coating layer 12 is the same as the average pore size on the first surface 21 of the substrate 2 or is smaller than the average pore size on the first surface 21 of the substrate 2, and the filtration performance of the coating layer 12 is improved. The ratio may be 0.05 or more and 0.8 or less, 0.1 or more and 0.5 or less, or 0.2 or more and 0.4 or less.

[0059] [Embodiment 2: Composite Porous Body] ≪Base material≫ In the second embodiment, a tubular composite porous body 1 will be described with reference to Fig. 4. The shape of the substrate 2 of this composite porous body 1 is tubular. A first surface 21 of the tubular substrate 2 constitutes the outer peripheral surface of the substrate 2. A coating layer 12 formed on the first surface 21 constitutes the outer peripheral surface of the tubular composite porous body 1. The composite porous body 1 of the second embodiment can have the same configuration as that of the first embodiment, except that the shape of the substrate 2 is tubular.

[0060] The tubular composite porous body 1 may be arranged in a bent state, for example, in a module of a purification device. Therefore, resistance to bending may be required even for the tubular composite porous body 1. The bending resistance of the tubular composite porous body 1 may be evaluated, for example, by winding the composite porous body 1 around the outer peripheral surface of a cylinder having a predetermined radius.

[0061] [Embodiment 3: Separation membrane] The separation membrane according to the third embodiment is a separation membrane including the composite porous body of the first or second embodiment, and the separation membrane is a pervaporation membrane or a steam filtration membrane. The composite porous body of the first or second embodiment has a good fluid permeation rate even when the fluid is other than gas. Therefore, the pervaporation membrane using the composite porous body of the first or second embodiment can have a good fluid permeation rate. Furthermore, the composite porous body of the first or second embodiment has an improved fluid permeation rate when the fluid is gas. Therefore, the steam filtration membrane using the composite porous body of the first or second embodiment can have a high fluid permeation rate.

[0062] [Embodiment 4: Separation membrane] The separation membrane according to embodiment 4 is a separation membrane including the composite porous body of embodiment 1 or embodiment 2, and the separation membrane is an ultrafiltration membrane, a microfiltration membrane, a nanofiltration membrane, or a particle separation membrane. The composite porous body of embodiment 1 or embodiment 2 has a good fluid permeation rate even when the fluid is other than gas. Therefore, the ultrafiltration membrane, the microfiltration membrane, the nanofiltration membrane, or the particle separation membrane using the composite porous body of embodiment 1 or embodiment 2 can have a good fluid permeation rate.

[0063] [Embodiment 5: Method for producing a composite porous body] The method for producing a composite porous body according to embodiment 5 is the method for producing the composite porous body according to embodiment 1 or embodiment 2, A step A of preparing a substrate having a first surface, the substrate being made of a porous material made of polytetrafluoroethylene; A step B of preparing a coating liquid containing a compound having a siloxane bond; A step C of applying the coating liquid to at least a portion of the first surface; A step D of crosslinking a portion of the coating liquid applied to the substrate; and a step E of washing away the coating liquid that has been applied to the substrate and that has not been crosslinked and remains in the step D to form a coating layer that covers at least a portion of the first surface of the substrate, thereby obtaining a composite porous body. This is a method for producing a composite porous body, wherein the time from the end of step D to the start of step E is 48 hours or less.

[0064] <Process A> In step A, a substrate 2 having a first surface 21 and made of a porous material made of polytetrafluoroethylene is prepared. The substrate 2 is the same as the substrate 2 provided in the composite porous material 1 described in embodiment 1 or embodiment 2.

[0065] The method for producing the substrate 2 is not particularly limited. For example, the substrate 2 may be produced by the manufacturing method disclosed in JP 2010-94579 A. Specifically, a thin film made of PTFE is stretched to make the thin film porous. As a result, the substrate 2 made of a porous PTFE body is obtained. The average pore size of the substrate 2 changes depending on the stretching conditions.

[0066] <Process B> In step B, a coating liquid containing a compound having a siloxane bond is prepared. Examples of coating liquids containing a compound having a siloxane bond include oil-type polydimethylsiloxane (PDMS), oil-type phenylmethylsiloxane, oil-type vinyl-terminated polydimethylsiloxane (vinyl-terminated PDMS), oil-type trimethoxysilyl-terminated polydimethylsiloxane, and oil-type hexamethyldisiloxane (HMDSO). These coating liquids may be diluted in a solvent such as hexane or toluene before coating.

[0067] The viscosity of the coating liquid at 25° C. may be 1 Pa·s or more and 10,000 Pa·s or less. This makes it easier to form a thin coating layer 12.

[0068] <Process C> In step C, the coating liquid prepared in step B is applied to at least a part of the first surface 21 of the substrate 2 prepared in step A. The coating liquid can be applied to the first surface 21 by any method. The coating method is, for example, spin coating, bar coating, dip coating, or die coating. The substrate 2 in a tube or sheet shape may be fixed to a rotating shaft, and the coating liquid may be applied by spraying while rotating the substrate 2. In order to form a thin coating layer 12 over a relatively large area, bar coating is preferred. Bar coating, in which the coating liquid is dropped onto the substrate 2 and then spread with a bar, can apply the coating liquid thinly and uniformly over a wide area. The bar groove depth of the bar coating can be, for example, 1 μm to 1000 μm, or 10 μm to 100 μm.

[0069] <Process D> In step D, a part of the coating liquid applied to the substrate 2 is crosslinked. For example, the surface of the coating liquid is irradiated with plasma to crosslink a part of the coating liquid.

[0070] The conditions of the plasma irradiation are appropriately adjusted so as to crosslink a part of the coating liquid applied to the substrate 2. For example, the following conditions can be used. Gases: inert gases (nitrogen, helium, etc.), hydrocarbon gases (ethylene, butadiene, etc.), organosilicon compounds (hexamethyldisiloxane (HMDSO), etc.) Gas flow rate: 100sccm~400sccm Pressure: 10Pa~50Pa Output: 100W~300W Stage feed speed (inversely proportional to plasma exposure time): 1m / min~10m / min Plasma exposure time: 0.05 to 1 minute The plasma gas may be a mixed gas, which allows the thickness and composition of the outermost layer to be appropriately changed.

[0071] <Process E> In step E, the coating liquid that has been applied to the substrate 2 and that has not been crosslinked and remains in step D is washed away to form a coating layer 12 that covers at least a portion of the first surface 21 of the substrate 2, thereby obtaining a composite porous body 1.

[0072] Examples of the cleaning method include a method in which the composite porous body 1 is set in a filtration device and then a cleaning liquid such as hexane is passed through it by pressure filtration or vacuum filtration to clean it, and a method in which the composite porous body 1 is immersed in a cleaning liquid such as hexane to clean it.

[0073] The time from the end of step D to the start of step E is 48 hours or less. When the time from the end of step D to the start of step E is 48 hours or less, the coating liquid can be in a state where a part of it is crosslinked and the rest is not crosslinked. By washing away the coating liquid that remains uncrosslinked, a thin coating layer 12 can be formed on at least a part of the first surface 21 of the substrate 2. When the composite porous body 1 having the thin coating layer 12 is used as a material for a separation membrane, it can provide a separation membrane having a good fluid permeation rate.

[0074] The time from the end of step D to the start of step E is 48 hours or less, may be 24 hours or less, or may be 12 hours or less. The lower limit of the time from the end of step D to the start of step E is not particularly limited, and may be 0 hours or more. The time from the end of step D to the start of step E is 0 hours or more and 48 hours or less, may be 0 hours or more and 24 hours or less, or may be 0 hours or more and 12 hours or less. If the time from the end of step D to the start of step E exceeds 48 hours, crosslinking of the coating liquid proceeds, the thickness of the crosslinked portion increases, and the thickness of the coating layer increases. If a composite porous body with an increased thickness of the coating layer is used as a material for a separation membrane, the permeation rate of the fluid through the separation membrane decreases. EXAMPLES

[0075] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.

[0076] [Preparation of composite porous bodies] <Samples 1 to 6, Sample 101> Each sample of composite porous body was produced according to the following steps A to E.

[0077] <Process A> In step A, a sheet-like substrate made of a porous material composed of polytetrafluoroethylene was prepared. The average pore size on the first surface of the substrate and the average thickness of the substrate for each sample are as shown in the "Average pore size on the first surface" and "Average thickness" columns of "Substrate" in Table 2.

[0078] <Process B> In process B, an oil-like coating liquid was prepared. The type of coating liquid used for each sample is as shown in the "Process B" column in Table 1. The viscosity of the coating liquid at 25°C was 1 Pa·s to 10,000 Pa·s.

[0079] [Table 1]

[0080] <Process C> In step C, the coating liquid was applied to the first surface of the substrate by bar coating. The depth of the bar groove was 30 μm.

[0081] <Process D> In step D of Samples 1 to 6, the surface of the coating liquid was irradiated with plasma to crosslink a part of the coating liquid. The conditions of the plasma irradiation (gas type, gas flow rate, pressure, output, stage feed speed, plasma irradiation time) are as shown in the "Step D" column of Table 1.

[0082] In step D of Sample 101, the surface of the coating liquid was irradiated with an electron beam to crosslink a part of the coating liquid. The conditions of the electron beam irradiation were an acceleration voltage of 150 kV and a dose of 1000 kGy.

[0083] <Process E> In step E, the coating liquid that was applied to the substrate and that remained uncrosslinked in step D was washed away to form a coating layer that covered at least a part of the first surface of the substrate, thereby obtaining a composite porous body for each sample. The composite porous body was immersed in hexane for washing. The time from the end of step D to the start of step E is as shown in the "Time" column of "Steps DE" in Table 1.

[0084] <Sample 102> As sample 102, a composite hard body was prepared by the method described in Example 1 of Patent Document 1 (JP Patent Publication 2009-208079 A). Specifically, the mixing ratio of an organopolysiloxane (HMS-301) having two or more hydrosilyl groups and an organopolysiloxane (DMS-V35) having two or more vinyl groups was adjusted so that the hydrosilyl group was 1 mol per 1 mol of vinyl group based on the analysis results described in Tables 3 and 4 of Patent Document 1. Furthermore, a platinum complex catalyst (divinyltetramethyldisiloxane platinum complex) was added at a concentration of 200 ppm relative to the total amount of polysiloxane used, and then isooctane was added to make a 10 wt% solution. This solution was preheated at 80°C for 300 seconds before coating. Immediately after heating, a required amount of isooctane was added to make the overall concentration 5 wt%. The prepared coating solution was applied by bar coating to a sheet-like substrate made of a porous material composed of polytetrafluoroethylene, and then dried by heating at 80° C. for 15 minutes.

[0085] [evaluation] <Average thickness and average pore size of coating layer> The average thickness and average pore size of the coating layer were measured for each sample of the composite porous body. The average thickness of the coating layer was measured by SEM. The average pore size of the coating layer was measured by a liquid passage test. The specific measurement method is as described in the first embodiment. The results are shown in Table 2. In all samples, the average pore size of the substrate was larger than the average pore size of the coating layer.

[0086] [Table 2]

[0087] <Measurement of permeation flux of permeate through composite porous material> The permeation flux of each composite porous body was measured using hexane as the permeating liquid. The permeation flux F indicates the amount of solution permeated W per unit time t and unit area A, and is expressed by the following formula: F=W / t A The higher the permeation flux, the higher the fluid permeation rate through the composite porous body. The permeation flux of each sample is shown in Table 2.

[0088] <Consideration> The composite porous bodies of Samples 1 to 6 correspond to Examples. The composite porous bodies of Samples 101 and 102 correspond to Comparative Examples. It was confirmed that the composite porous bodies of Samples 1 to 6 (Examples) had a higher permeation flow rate than the composite porous bodies of Samples 101 and 102 (Comparative Examples), and had a good fluid permeation rate.

[0089] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways.

[0090] The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]

[0091] 1. Composite porous bodies 2 Base material 2h void 2A First layer 2B Second layer 7 Test Equipment 12 Covering layer 21 Front page 22 Second side 3h opening hole 30 surface 70 flasks 70U top opening 71 Chamber 71D Bottom opening

Claims

1. A substrate having a first surface and a coating layer covering at least a portion of the first surface, The substrate is a porous body made of polytetrafluoroethylene, The coating layer is made of a crosslinked polymer compound having a siloxane bond, The average thickness of the coating layer is 10 nm or more and 2000 nm or less, A composite porous body, wherein the average pore size on the first surface of the substrate is 50 nm or more and 500 nm or less.

2. The composite porous body according to claim 1 , wherein the crosslinked polymer compound is polydimethylsiloxane.

3. The composite porous body according to claim 1 or 2, wherein the coating layer has an average pore size of 1 nm or more and 50 nm or less.

4. The composite porous body according to claim 1 or 2, wherein the average thickness of the substrate is 1 μm or more and 100 μm or less.

5. 3. The composite porous body according to claim 1, wherein the coating layer has an average thickness of 10 nm or more and 180 nm or less.

6. The composite porous body according to claim 1 or 2, wherein the substrate is in the form of a sheet.

7. The substrate has a tube shape, The composite porous body according to claim 1 or 2, wherein the first surface is an outer peripheral surface of the tube.

8. The substrate comprises a first layer including the first surface and a second layer adjacent to the first layer; 3. The composite porous body according to claim 1, wherein the average pore size of the second layer is larger than the average pore size of the first layer.

9. A separation membrane comprising the composite porous body according to claim 1 or 2, The separation membrane is a pervaporation membrane or a vapor filtration membrane.

10. A separation membrane comprising the composite porous body according to claim 1 or 2, The separation membrane is an ultrafiltration membrane, a microfiltration membrane, a nanofiltration membrane or a particle separation membrane.

11. A method for producing the composite porous body according to claim 1 or 2, comprising the steps of: A step A of preparing a substrate having a first surface, the substrate being made of a porous material made of polytetrafluoroethylene; A step B of preparing a coating liquid containing a compound having a siloxane bond; A step C of applying the coating liquid to at least a portion of the first surface; A step D of crosslinking a portion of the coating liquid applied to the substrate; and a step E of washing away the coating liquid that has been applied to the substrate and that has not been crosslinked and remains in the step D to form a coating layer that covers at least a portion of the first surface of the substrate, thereby obtaining a composite porous body. The method for producing a composite porous body, wherein the time from the end of the step D to the start of the step E is 48 hours or less.

12. The method for producing a composite porous body according to claim 11 , wherein in the step D, the coating liquid is irradiated with plasma to crosslink a part of the coating liquid.

Citation Information

Patent Citations

  • Gas separation membrane

    JP2009208079A